Adaptive Children'S Management Of Special Education In Special Research School Inclusive Education (Case Study of Management of Adaptive Physical Education at Organizing Middle School Inclusive Education in Boyolali Regency) - Hastata, Limpat Tri; Sugiyanto, Sugiyanto; Hidayatullah, M. Furqon (Journal of Education, Health and Sport, 2019)
The purpose of this study was to find out: (1) Planning, (2) Organizing, (3) Implementation, and (4) Monitoring of Adaptive Physical Education in Middle School Providers of Inclusive Education in Boyolali District. This research was conducted in junior high school inclusive education providers in Boyolali Regency. This study uses qualitative research using a case study approach. Sampling and data sources using purposive sampling and snowball sampling methods. The technique of collecting data uses observation, interviews, and documentation. Data analysis in this study is data collection, data reduction, data presentation, and conclusion. The results of research on inclusive education in Boyolali Regency show that the management system of inclusive education in junior high schools in Boyolali Regency still has many weaknesses, especially in terms of process implementation. There are only a few schools that have planned management in implementing adaptive physical education. In organizing there is only an organizational structure and there is also a school team tasked with planning, drafting, developing and adjusting inclusive programs involving principals, class teachers, subject teachers, and parents of students. Exposure does not work properly because of the absence of special accompanying teachers and a lack of government attention, so schools cannot yet carry out education that is in accordance with the principle of inclusion in fulfilling children's educational rights. In the implementation of adaptive physical education learning has not been right on target and optimally related to services to children with special needs, in terms of the provision of material has not been adapted while in the use of infrastructure facilities there are still not many modifications in accordance with the needs of children with special needs taught. Supervision carried out only monitors the state of the school and does not see the management system. Adaptive physical education supporting resources are inadequate and still must be considered in terms of procurement and modification of facilities and infrastructure.